Intellectual Capital, Leverage dan Profitabilitas Perusahaan Sub-Sektor Asuransi di Bursa Efek Indonesia - Paramita, Putu Winda Agastya; Putri, I Gusti Ayu Made Asri Dwija (E-Jurnal Akuntansi, 2020)
The company's financial performance can be used as a tool to measure the overall level of health of a company. One indicator that is often used to measure a company's financial performance is profitability. Profitability is the level of a company's ability to generate profits and measure operational efficiency and the efficiency of the use of its assets. There are several factors that are thought to affect profitability including intellectual capital and leverage. This study aims to determine the effect of intellectual capital and leverage on company profitability. This research was conducted on 11 insurance sub-sector companies listed on the Indonesia Stock Exchange in 2016-2018. The sampling technique used is non probability sampling with the purpose sampling method. The analysis technique used in this study is multiple linear regression. The final results show that intellectual capital has a positive effect on profitability and leverage has a negative effect on company profitability. Keywords: Intellectual Capital; Leverage; Profitability.